Examination Anxiety Among in-School Adolescents: Parental Factors, School Environment and Gender as Determinants - Habeeb Omoponle Adewuyi; Moromoke Nimota Raji; Babatunde Adewole Ajani; Sylvester E. Umanhonlen; Ayodeji Solomon Adegoke (Indonesian Gender and Society Journal, 2023)
This study is motivated by the high level of test anxiety felt by learners in educational institutions, which can hurt their academic achievement and emotional well-being. This study aims to examine (parental factors, school environment, and gender) as determinants of test anxiety among secondary school students. This study used a descriptive survey with a correlational type of design. Secondary school adolescents were the target population of this study. A total of 285 responses were considered sufficient and included in the study, bringing the sample size to 300 respondents. To select the respondents, the researcher used a multi-stage sampling technique. The data collection method used was a questionnaire. Descriptive statistics (frequency counts and percentages) were used to analyze the questionnaire data and determine demographic information. The results stated that girls showed a higher tendency to experience test anxiety. Parental factors and school environment have a relative influence on the prediction of test anxiety. Gender had no significant relative impact on predicting test anxiety. This study underscores the need for cooperation between home and school to keep students focused on their education. They should also encourage, inspire and equip students with adequate motivation to reduce anxiety during exams.